Asian Provident Funds : Meeting Tomorrow’s Challenges - Jackson, Richard; Inglis, Evan (World Bank, Washington, DC, 2021)
Across the emerging world, policymakers are grappling with how to build retirement systems that meet the needs of their rapidly developing and rapidly aging societies. Nowhere is the challenge more urgent than in Asia, which is both developing and aging more rapidly than anywhere else on earth. Provident funds, which are fully funded, government-managed, defined contribution systems, have long been the dominant form of retirement provision in much of Asia. The purpose of this report is to assess the strengths and weaknesses of the provident fund model, evaluate the performance of three of Asia’s four largest provident funds, and identify steps that they and other provident funds can take to improve retirement security. The funds covered in the report are India’s Employees’ Provident Fund (EPF), Indonesia’s Jaminan Hari Tua (JHT), and Malaysia’s Employees Provident Fund (EPF). The report identifies two key features of the provident fund model that may make it an attractive choice for both governments and workers in emerging markets.